2015
DOI: 10.1002/jez.b.22663
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the invertebrate sea urchin P16 protein into mammalian MC3T3 osteoblasts transforms and reprograms them into “osteocyte‐like” cells

Abstract: P16 is an acidic phosphoprotein important in both sea urchin embryonic spicule development and transient mineralization during embryogenesis, and syncytium formation and mineralization in mature urchin tooth. Anti-P16 has been used to localize P16 to the syncytial membranes and the calcite mineral. Specific amino acid sequence motifs in P16 are similar to sequences in DSPP a protein common to all vertebrate teeth, and crucial for their mineralization. Here we examine the effect of P16 on vertebrate fibroblasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…There is little evidence in the literature for the specific involvement of the CDKN2A locus in bone metabolism, although p16 INK4a expression has been linked to altered osteoblast morphology and senescence in animal models, and one study identified transitional hypomethylation of CDKN2A in human bone marrow stromal cells in their differentiation toward an osteoblastic lineage . However, the importance of cyclin‐dependent kinases and their inhibitors has been demonstrated by studies of the osteogenic differentiation of adipose‐derived mesenchymal stem cells, in which the promoters of RUNX2 , osteocalcin , and osterix genes are actively demethylated in a process dependent upon growth arrest and DNA‐damage‐inducible protein, GADD45, which is known to interact with both CDK1 and CDKN1A .…”
Section: Discussionmentioning
confidence: 99%
“…There is little evidence in the literature for the specific involvement of the CDKN2A locus in bone metabolism, although p16 INK4a expression has been linked to altered osteoblast morphology and senescence in animal models, and one study identified transitional hypomethylation of CDKN2A in human bone marrow stromal cells in their differentiation toward an osteoblastic lineage . However, the importance of cyclin‐dependent kinases and their inhibitors has been demonstrated by studies of the osteogenic differentiation of adipose‐derived mesenchymal stem cells, in which the promoters of RUNX2 , osteocalcin , and osterix genes are actively demethylated in a process dependent upon growth arrest and DNA‐damage‐inducible protein, GADD45, which is known to interact with both CDK1 and CDKN1A .…”
Section: Discussionmentioning
confidence: 99%